NILAI PERJUANGAN TOKOH UTAMA PADA NOVEL LAUT TENGAH KARYA BERLIANA KIMBERLY (TINJAUAN SOSIOLOGI SASTRA) - Syahwardi, Sulthaanika Ferdy; Riansi, Erwin Salpa (Universitas Islam Sumatera Utara, 2024)
This research describes the value of the main character's struggle in the novel Laut Tengah by Berliana Kimberly using qualitative methods and a literary sociology approach. Data collection techniques are reading and note-taking techniques. Based on the data found, it can be concluded that the struggle values of the main characters in the novel Laut Tengah by Berliana Kimberly are as follows (1) the value of being willing to sacrifice is 5 data, (2) the value of unity is 1 data, (3) the value of respect is 2 data, (4) the value of patience is 3 data, (5) the value of the spirit of never giving up is 4 data, (6) the value of cooperation is 2 data. So it can be concluded that the researcher found the value of the main character's struggle in the novel Laut Tengah by Berliana Kimberly with 17 pieces of data.